2022
DOI: 10.1038/s41467-022-33597-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based modulation of CD4+ T cell effector and helper functions enhances adoptive immunotherapy

Abstract: Helper (CD4+) T cells perform direct therapeutic functions and augment responses of cells such as cytotoxic (CD8+) T cells against a wide variety of diseases and pathogens. Nevertheless, inefficient synthetic technologies for expansion of antigen-specific CD4+ T cells hinders consistency and scalability of CD4+ T cell-based therapies, and complicates mechanistic studies. Here we describe a nanoparticle platform for ex vivo CD4+ T cell culture that mimics antigen presenting cells (APC) through display of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, MoDCs may be dysfunctional, for example, due to the presence of the tumor microenvironment ( Veglia and Gabrilovich, 2017 ). Moreover, several antigen-specific expansion approaches using artificial APCs (aAPCs) and cell-free systems have been described ( Ichikawa et al, 2020 ; Isser et al, 2022 ; Sun et al, 2022 ). The application of APCs or aAPCs introduces difficulties related to proliferation and the consumption of growth factors, while cell-free approaches require the laborious conjugation of pMHCs or costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MoDCs may be dysfunctional, for example, due to the presence of the tumor microenvironment ( Veglia and Gabrilovich, 2017 ). Moreover, several antigen-specific expansion approaches using artificial APCs (aAPCs) and cell-free systems have been described ( Ichikawa et al, 2020 ; Isser et al, 2022 ; Sun et al, 2022 ). The application of APCs or aAPCs introduces difficulties related to proliferation and the consumption of growth factors, while cell-free approaches require the laborious conjugation of pMHCs or costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The potency of T-cell stimulation relies on the high density of pMHC presentation, closely mimicking the role of the secondary lymphoid organs as the primary sites for naïve T-cell antigenic engagement ( González et al, 2005 ). To circumvent the drawbacks associated with the use of cells and create a high-density antigenic environment, various cell-free systems employing nano/micro-particles have been developed ( Singha et al, 2017 ; Rhodes et al, 2021 ; Isser et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this TiO 2 , there will be no loss in cell viability, and Jurkat T cells can produce higher cytokines in cancer immunotherapy . Schneck et al have shown the use of Jurkat T cells in adoptive T cell therapy by using iron-dextran nanoparticles coated with MHC II and costimulatory proteins to enhance CD8 + T cell cells activity, leading to an increased cytokine production and memory formation to kill cancer cells more efficiently . Many combined blockade therapy approaches are also being followed, such as PD-1/PD-L1 blockage or triple blockade of CTLA-4, PD-L1, and TIM3 receptors, in order to enhance the functions of T cells. , Researchers are also exploring combinations of CAR-T cell therapy with other treatments such as immune checkpoint inhibitors and targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Scaling down the size of aAPCs to the nanoscale is a promising alternative approach since it provides an appropriate length scale for costimulation and higher ligand densities. Nanosized aAPCs including iron oxide, , lipid nanoparticles, and DNA origamis have shown successful expansion of T-cells. In the presence of nanoscale aAPCs, signaling molecules form a stable membrane domain with an average radius of 35–70 nm, and nanoparticles with ligand spacing similar to these domains result in enhanced T-cell activation .…”
mentioning
confidence: 99%